Prognosa Banjir Sub Das Konto Menggunakan Simodas - Ruslan Wirosoedarmo; Alexander Tunggul Sutan Haji; Kuswadi Kuswadi (agriTECH, 2012)
The problem of fl ood and drought give negative impact to water system in the catchment area. It is related to forest condition in the upstream of watershed. One cause of flooding is the use of land that does not comply with the environmental carrying capacity making the area of repage is reduced. The purpose of this research is to predict the increase of flood hydrograph due to the change of land use sub-watershed. This study used spatial and attribute data. Spatial data included digital maps of topography, digital river network map, digital map of soil types, and digital maps land use. Map of land use consisted of the existing conditions of land use, while the land use itself was based on the 2010-2030 Spatial Plan of Malang Regency. Attribute data in the form of sub-daily rainfall data in Konto watershed year 2001-2010 were collected from the Pujon and Kedungrejo station. Data was analized using SIMODAS. Result indicated that changes of land use in sub-watershed Konto in Malang Regency for 20 years (2010-2030) increase the peak of fl ood from 1014,70 m3/ second to 1101,27 m3/ second or up to 8.53 %.ABSTRAKBanjir dan kekeringan merupakan dampak dari buruknya sistem tata air sebuah DAS. Hal tersebut berkaitan dengan kondisi hutan di bagian hulu DAS. Salah satu penyebab bencana banjir yaitu pemanfaatan lahan yang tidak sesuai dengan daya dukung lingkungan, sehingga kawasan resapan air berkurang. Tujuan penelitian adalah memprediksi peningkatan hidrograf banjir karena pengaruh perubahan alih fungsi lahan di Sub DAS Konto. Penelitian ini menggunakan data spasial dan data atribut. Data spasial antara lain peta digital topografi , peta digital jaringan sungai, peta digital jenis tanah, dan peta digital tata guna lahan. Peta tata guna lahan terdiri dari tataguna lahan kondisi eksisting dan tata guna lahan berdasarkan Rencana Tata Ruang Wilayah Kabupaten Malang tahun 2010-2030. Data atribut yaitu berupa data curah hujan harian wilayah Sub DAS Konto tahun 2001-2010 dari stasiun hujan Kedungrejo dan Pujon. Data dianalisis menggunakan metode analisa spasial dan disimulasi dengan SIMODAS. Hasil penelitian menunjukkan perubahan alih fungsi lahan selama 20 tahun (2010-2030) meningkatkan debit puncak banjir dari 1014,704 m3/detik menjadi 1101,27 m3/detik atau naik sebesar 8,53 %.